ANALISIS KINERJA BERBASIS BALANCED SCORECARD PADA KOPERASI XYZ - Lusi Setyandarini Surya, Luh Putu (E-Jurnal Akuntansi; Vol 8 No 2 (2014), 2014)
Cooperatives require precise measurement of performance as the basis for determining the effectiveness of its business activities, not only be seen from its financial performance, but also from the other perspectives, such as, learning and growth, internal business processes, and customer. Therefore, Balanced Scorecard -based performance measurement can be used as a measurement of the performance of cooperatives. In this study intended to determine the performance of the XYZ cooperation, using the perspectives of balanced scorecard. The research methods used are Employee Satisfaction Index (ESI), employee’s productivity, growth level of business, growth level of member as a customer, Customer Satisfaction Index (CSI), Return on Equity (ROE) and the average of net income. Based on the analysis, it is known that the performances based on the perspectives of balanced scorecard are varied. There is a reduction in the financial performance, whereas the other perspectives showing good performances.
Keywords: performance, balanced scorecard.